2021
DOI: 10.1139/facets-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Seeking shelter: homelessness and COVID-19

Abstract: Those experiencing homelessness in Canada are impacted inequitably by COVID-19 due to their increased exposure, vulnerability of environment and medical comorbidities, and their lack of access to preventive care and treatment in the context of the pandemic. In shelter environments one is unable to effectively physically distance, maintain hygiene, obtain a test, or isolate. As a result, unique strategies are required for this population to protect them and those who serve them. Recommendations are provided to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…There is a large body of evidence highlighting how communal forms of homelessness accommodation can lead to transmission of communicable diseases such as H1N1/swine flu [ 2 ], MRSA [ 38 ] and tuberculosis [ 39 ]. Furthermore, a recent systematic review concluded that use of accommodation that satisfies basic needs such as a bed and food—as is the case with shelters—can do more harm than no intervention at all [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large body of evidence highlighting how communal forms of homelessness accommodation can lead to transmission of communicable diseases such as H1N1/swine flu [ 2 ], MRSA [ 38 ] and tuberculosis [ 39 ]. Furthermore, a recent systematic review concluded that use of accommodation that satisfies basic needs such as a bed and food—as is the case with shelters—can do more harm than no intervention at all [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns centred upon people who were literally roofless and those in communal forms of accommodation, such as shelters and hostels, where facilities and air space were shared. It was feared these environments could hamper a person’s ability to adhere to public health instructions regarding hand hygiene, maintaining physical distancing, and isolation when symptomatic or following a positive SARS-CoV-2 test [ 1 , 2 ]. The COVID-19 pandemic triggered unprecedented policy and practice responses, with homelessness being reframed as an urgent public health crisis for the very first time [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, emerging evidence suggests that the experience of homelessness itself has changed since the COVID-19 pandemic. There appears to be greater visibility in rural settings (Devereaux 2021;Schiff et al 2020) where previously homelessness was either not present or hidden, more reliance on temporary hotel accommodations or urban camping in avoidance of emergency shelters or as a result of reduction in affordable housing (Baral et al 2021;Devereaux 2021) and potentially more reliance on hospitalbased care due to reductions in or closures of homeless-serving programs and services (Gibson et al 2020;Perri et al 2020). If these changes persist, the algorithm may perform differently than before the pandemic.…”
Section: Future Opportunitiesmentioning
confidence: 99%
“…For isolation or quarantine, several authorities in the U.S. have secured hotels to house people experiencing homelessness temporarily (Fuchs et al, 2021). Likewise, in Canada, isolation units and shelters were set up from hotels or community centers (Baral et al, 2021).…”
Section: Emergency Responses To Homelessness Regarding Covid-19mentioning
confidence: 99%
“…The risks of SARS-CoV-2 infection and the course of the COVID-19 disease and prevention measures are extremely unequally stratified among socioeconomic groups (Coughlin, Sandel & Stewart, 2020;Baral et al, 2021). Thus, precisely the most vulnerable social groups were hit particularly hard by the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%